Analysis of customer mindset change and accounting practice of garbage bank as medium of edupreneurship. (2015) - Purwaningsih, Anna
This study aims to determine: (1) whether there is a change in individuals' mindset associated with the existence of garbage bank and (2) the accounting practices in Garbage Bank of Badegan (GBB). Garbage bank is the manifestation of public awareness to actively address the issue of garbage management. Thus, garbage bank is a medium for communal education and entrepreneurship. Its concept basically adopts the banking concept. It is not the money which is saved but garbage. This research was conducted at the Gemah Ripah GBB in Bantul, Indonesia by distributing questionnaires to customers. Change of mindset is viewed from environmental and the economic standpoint. Data processing employed the pair sample t-test. The results showed that there was a change in the public mindset before and after joining GBB. Garbage is no longer burned or thrown into the river, but it is managed into value added products.